Recent advances in oncolytic virus therapy for hepatocellular carcinoma - Zhu, Licheng; Lei, Yu; Huang, Jia; An, Yahang; Ren, Yanqiao; Chen, Lei; Zhao, Huangxuan; Zheng, Chuansheng (Frontiers in Oncology, 2023)
Hepatocellular carcinoma (HCC) is a highly refractory cancer and the fourth leading cause of cancer-related mortality worldwide. Despite the development of a detailed treatment strategy for HCC, the survival rate remains unsatisfactory. Oncolytic virus has been extensively researched as a new cancer therapeutic agent in the treatment of HCC. Researchers have designed a variety of recombinant viruses based on natural oncolytic diseases, which can increase the targeting of oncolytic viruses to HCC and their survival in tumors, as well as kill tumor cells and inhibit the growth of HCC through a variety of mechanisms. The overall efficacy of oncolytic virus therapy is known to be influenced by anti-tumor immunity, toxic killing effect and inhibition of tumor angiogenesis, etc. Therefore, a comprehensive review of the multiple oncolytic mechanisms of oncolytic viruses in HCC has been conducted. So far, a large number of relevant clinical trials are under way or have been completed, and some encouraging results have been obtained. Studies have shown that oncolytic virus combined with other HCC therapies may be a feasible method, including local therapy, chemotherapy, molecular targeted therapy and immunotherapy. In addition, different delivery routes for oncolytic viruses have been studied so far. These studies make oncolytic virus a new and attractive drug for the treatment of HCC.